Isolation of Trueperella pyogenes in a case of thoracic and abdominal abscess in a galago (Otolemur garnettii). Issue 4 (24th June 2016) - Salleng, Kenneth J.; Burton, Bryce J.; Apple, Troy M.; Sanchez, Susan
Abstract: Background: An adult male galago ( Otolemur garnettii ) presented for fight wounds following pairing for breeding. Treatment was symptomatic with recovery. Following resolution, the animal re‐presented and died, despite additional treatment. Methods: Necropsy, histopathology, bacterial cultures, and 16S RNA sequencing. Results: A large intrathoracic/intra‐abdominal abscess due to Trueperella pyogenes was found at necropsy. Conclusions: T. pyogenes should be considered in abscesses/wounds of galagos.